PEMBENTUKAN KARAKTER IDIOLOGI MODERAT DI PESANTREN NGALAH PURWOSARI PASURUAN - Nafilatul Fitriyah; Muhammada (AL MURABBI, 2019)
Every human being must have different characters. From these different characters can also make a difference that can lead to division. However, if the character differences can be harmonized with the formation of characters that are continuous and are continuous. Because of the formation of characters that are only half-done, it will make someone not only misunderstood but understand wrong. Based on the results of the data obtained stating the character of the santri can be formed with several attitudes to make it towards moderate character. As with applying the attitude of love of God, and all its creation, honesty / trust, respect and courtesy, tolerance, please help and mutual cooperation / cooperation, fairness, the spirit of nationalism, love of peace. The attitude is applied in the daily activities of the santri, the weekly activities of the santri, the monthly activities of the santri, the annual activities of the santri and activities that are incidental.